Incidence, survival and stage at diagnosis of small intestinal neuroendocrine tumours in Queensland, Australia, 2001‐2015. Issue 4 (10th February 2021) - Wyld, David; Moore, Julie; Tran, Nancy; Youl, Philippa
Abstract: Aim: Multiple studies have observed increasing incidence of small intestinal (SI) neuroendocrine tumours (NETs). The aim of this study was to describe incidence, mortality and survival of SI NETs by sub‐site and stage at diagnosis. Methods: Data on patients diagnosed with SI NETs between 2001 and 2015 were sourced from the Queensland Oncology Repository. Staging algorithms utilising several data sources were used to calculate stage at diagnosis (localised, regional or metastatic disease). Results: We identified 778 SI NETs and of those 716 (92%) had either a documented or derived stage. Incidence doubled from 0.68 per 100 000 to 1.42 per 100 000 over the 15‐year period. Most common site was ileum (49.1%) and 84.2% were of carcinoid morphology type. Stage at diagnosis was calculated for 91.7% of patients with 28.3% presenting with regional involvement and 23.9% with distant metastasis. Risk factors associated with metastatic disease were jejunal and SI site not otherwise specified, neuroendocrine carcinoma histology and residing in a rural area. Increasing incidence of localised disease and a corresponding reduction in metastatic disease was observed over time. Five‐year cause‐specific survival for patients diagnosed between 2001 and 2005 was 82.5%, increasing to 93.8% from 2011 to 2015. Survival was lowest for those with metastatic disease (74.2%). Survival increased between 2001 to 2005 and 2011 to 2015 for each disease stage. Conclusions: SI NET incidence in Queensland doubled between 2001 and 2015. Survival was high and improved over time.